PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI BUKU SAHAM PADA PERUSAHAAN MANUFAKTUR PERIODE 2015-2019 (Studi Empiris Pada Sub Sektor Logam Yang Terdaftar Di BEI) - Nazariah Nazariah; Ramzijah Ramzijah; Nurjamaliah Nurjamaliah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to examine the capital structure and financial performance of the book value of shares in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This type of research is a type of quantitative research. This population and sample are all manufacturing companies in the metal sub-sector listed on the Indonesia Stock Exchange, totaling 15 companies. The Sampling technique used purpovise sampling method. the results of the capital structure variable (X1) had no significant effect on the book value of the shares. For the financial performance variable (X2), had no significant effect on the book value of the stock. Capital structure (X1) and financial performance (X2) have no simultaneous effect on the book value of the shares.Keywords: Capital structure, Financial performance and book value on shares